2021
DOI: 10.7717/peerj.10811
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the GRAS gene family reveals their contribution to the high adaptability of wheat

Abstract: GRAS transcription factors play important roles in many processes of plant development as well as abiotic and biotic stress responses. However, little is known about this gene family in bread wheat (Triticum aestivum), one of the most important crops worldwide. The completion of a quality draft genome allows genome-wide detection and evolutionary analysis of the GRAS gene family in wheat. In this study, 188 TaGRAS genes were detected and divided into 12 subfamilies based on phylogenetic analyses: DELLA, DLT, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 74 publications
(75 reference statements)
3
11
0
Order By: Relevance
“…However, motifs within different subfamilies were varied, which might be attributable to the diverse biological functions of GRASs. As reported previously, GRAS proteins were randomly distributed in the phylogenetic tree (To et al, 2020;, and had similar functions when they were in the same subfamily (Liu and Wang, 2021).…”
Section: Discussionsupporting
confidence: 64%
“…However, motifs within different subfamilies were varied, which might be attributable to the diverse biological functions of GRASs. As reported previously, GRAS proteins were randomly distributed in the phylogenetic tree (To et al, 2020;, and had similar functions when they were in the same subfamily (Liu and Wang, 2021).…”
Section: Discussionsupporting
confidence: 64%
“…In the region 2, 66.2-68.3 cM, the gene TraesCS2A01G099900 is a homologue of the TF genes of the EIN3/EIL family, which plays a key role in the ethylene signaling pathway, and the GRAS family of the DELLA subfamily, which is involved in hormonal signaling pathways mediated by gibberellic, jasmonic, abscisic, salicylic acids and ethylene. Genome-wide analyzes of these families in T. aestivum showed that chromosome 2A carries two genes of EIN3/EIL family [45] and 10 genes of the GRAS family [46]. The gene TraesCS2A01G099400 can be considered as a candidate controlling the trait TGW.…”
Section: Discussionmentioning
confidence: 99%
“…(2017) Sorghum bicolour (Indian millet) Poaceae Monocot 81 13 Fan et al. (2021b) Triticum aestivum (wheat) Poaceae Monocot 188 12 Liu and Wang (2021) Vitis vinifera (grape vine) Vitaceae Eudicot 52 13 Grimplet et al. (2016) Zea mays (maize) Gramineae Monocot 86 08 Guo et al.…”
Section: Gras Gene Family: Expansion and Diversification In The Plantsmentioning
confidence: 99%